2013
DOI: 10.1111/nyas.12318
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric anxiety disorders

Abstract: This article provides a brief review of the current available data concerning present treatment and potential new treatment advances for pediatric anxiety disorders, such as generalized anxiety disorder, separation anxiety disorder, social phobia, obsessive-compulsive disorder, and posttraumatic stress disorder. Disorder-specific treatment methods and innovations, particularly computer-assisted methods of delivery for cognitive behavioral therapy (CBT) will be reviewed. Additionally, the paper will discuss nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
0
17
0
1
Order By: Relevance
“…61,62 For adults, evidence-based pharmacotherapies are also available. These include benzodiazepine receptor agonist (BzRA) hypnotics (e.g., zolpidem, eszopiclone, zaleplon, temazepam, flurazepam, estazolam), doxepin, ramelteon, and suvorexant.…”
Section: Descriptionmentioning
confidence: 99%
“…61,62 For adults, evidence-based pharmacotherapies are also available. These include benzodiazepine receptor agonist (BzRA) hypnotics (e.g., zolpidem, eszopiclone, zaleplon, temazepam, flurazepam, estazolam), doxepin, ramelteon, and suvorexant.…”
Section: Descriptionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors do not appear to have an additive effect in the treatment of obsessive-compulsive disorder (OCD) if used in conjunction with exposure-based CBT [30]. Memantine, a noncompetitive antagonist of the NMDA receptor thought to protect neurons from the neurotoxic impact of glutamate, has had some promising treatment results for those whose OCD is refractory to other treatments [31,32].…”
Section: Pharmacological Treatment Options For Pediatric Anxiety Disomentioning
confidence: 99%
“…Pharmacotherapy should be considered if comorbid disorders are present, if there is a partial response to therapy, or if the symptoms increase in severity and a reduction in symptoms is needed to make progress in therapy. Recent randomized controlled trials have reported that treatment response is improved if both pharmacological and cognitive behavioral therapies are applied to the reduction of symptoms of anxiety [30].…”
Section: The American Academy Of Child and Adolescent Psychiatry Treamentioning
confidence: 99%
See 1 more Smart Citation
“…First, our working hypothesis for the mechanism of brain dysfunction induced by PNE is supported by the behavioral and pharmacological experiments with DCS as discussed above. Second, and most importantly, our findings also suggest that NMDA receptor partial agonists may be a novel and effective treatment for impaired attentional function, behavioral flexibility, and anxiety in patients with AD/HD or schizophrenia (Chue and Lalonde, 2014;Rapp et al, 2013). Accordingly, further studies using the PNE mouse model are warranted to clarify the pathophysiology and to provide the conceptual framework for drug discovery in neuropsychiatric disorders such as AD/HD and schizophrenia.…”
Section: Prenatal Nicotine Exposure Impairs Corticogenesismentioning
confidence: 99%